Effects of Variations of SUSY Breaking Scale on Neutrino Parameters at Low Energy Scale under Radiative Corrections - Kh. Helensana Devi; K. Sashikanta Singh; N. Nimai Singh (Advances in High Energy Physics)
The paper addresses the effects of the variations of the SUSY breaking scale ms in the range (2-14) TeV on the three neutrino masses and mixings, in running the renormalization group equations (RGEs) for different input values of high energy seesaw scale MR, and in both normal and inverted hierarchical neutrino mass models. The present investigation is a continuation of the earlier works based on the variation of ms scale. Two approaches are adopted one after another—bottom-up approach for running gauge and Yukawa couplings from low to high energy scale, followed by the top-down approach from high to low energy scale for running neutrino parameters defined at high energy scale, along with gauge and Yukawa couplings. A self-complementarity relation among three mixing angles is also employed in the analysis and it is found to be stable under radiative correction. Significant effect due to radiative corrections on neutrino parameters with the variation of SUSY breaking scale ms is observed. For comparison of the results, variation of tanβ for different MR is also considered.